2024
DOI: 10.1038/s41467-024-47935-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent TFIIH binding to non-excised DNA damage causes cell and developmental failure

Alba Muniesa-Vargas,
Carlota Davó-Martínez,
Cristina Ribeiro-Silva
et al.

Abstract: Congenital nucleotide excision repair (NER) deficiency gives rise to several cancer-prone and/or progeroid disorders. It is not understood how defects in the same DNA repair pathway cause different disease features and severity. Here, we show that the absence of functional ERCC1-XPF or XPG endonucleases leads to stable and prolonged binding of the transcription/DNA repair factor TFIIH to DNA damage, which correlates with disease severity and induces senescence features in human cells. In vivo, in C. elegans, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 112 publications
(201 reference statements)
0
1
0
Order By: Relevance
“…Another possibility would be that these rare phenotypes of XP/CS, despite showing normal clearance of RNAPII, are caused by the accumulation of other repair intermediates. Indeed, recent work revealed that the absence of ERCC1-XPF or XPG, but not XPA, leads to persistent binding of TFIIH to non-excised DNA damage, correlating with developmental arrest and neuronal dysfunction in nematodes 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be that these rare phenotypes of XP/CS, despite showing normal clearance of RNAPII, are caused by the accumulation of other repair intermediates. Indeed, recent work revealed that the absence of ERCC1-XPF or XPG, but not XPA, leads to persistent binding of TFIIH to non-excised DNA damage, correlating with developmental arrest and neuronal dysfunction in nematodes 41 .…”
Section: Discussionmentioning
confidence: 99%